Contribution of the Al-Qur'an to Religious Pluralism - Anas Bahtiar; Ahmad Arifi; Rachmad Resmiyanto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The aim of the research carried out by this author is none other than to find out the contribution of the Al-Qur'an in providing an understanding of religious pluralism. This is of course motivated by the existence of conflicts carried out by individuals in the name of Islam. So that the Islamic religion, which was originally a mercy to all nature, has now turned into something terrible thanks to the existence of this person. The research method used in this research is using research in the form of a research library/literature review. The data used in this research is divided into two parts, the first is primary data which consists of the Koran. Secondly, secondary data, namely data that supports valid data collection, this data consists of several books which include Jami' Al-Bayan Fi Ta'wil Al-Qur'an, Tafsir Baidhawi, Al-Kassyaf an Haqaiq Al- Tanzil Wa 'Uyun Al-Aqawil Fi Wujuh Al-Ta'Wil. Books and journals are related to the theme raised in this research, namely religious pluralism. The results of this research show that the contribution of the Koran to religious pluralism consists of three things. Firstly, recognizing other religions, secondly providing freedom of religion, thirdly respecting other religions. Thus, if someone commits violence in the name of Islam, then it is necessary to cross-check that person.